대동맥 혈관 경직도와 64 채널 다중 검출기 심장 전산화 단층 촬영에서 측정된 심외막 및 심장막주변 지방 조직과의 연관성 - 최태영 (The Graduate School, Ajou University, 2013)
Objectives: Increased measured vascular stiffness is an early marker of atherosclerosis and is associated with cardiovascular risk factors. Coronary artery calcium (CAC) and adipose tissues are accurate markers of overall burden of coronary atherosclerosis and metabolic status, respectively. We evaluated the relation of vascular stiffness with epicardial (EAT) and pericardial (PAT) adipose tissues, as well as the presence and severity of CAC. Methods: One hundred and eleven consecutive subjects, mean age 59±11 years, 78% male, underwent 64-multidetector row cardiac computed tomography (MDCT) and their carotid-radial pulse wave velocity (PWV) was measured using SphygmoCor tonometry. EAT and total thoracic adipose tissue (TAT) volumes were measured using MDCT. PAT was calculated as TAT – EAT. The highest tertile of EAT (≥ 111 ml) and PAT (≥ 103 ml) were defined as significant adipose tissue depots. Results: PWV was moderately associated with EAT (r=0.46, p<.001), and PAT (r=0.41, p<.001). PWV increased proportionally with the severity of CAC from 0-400+. The relative risk of highest vs. lowest tertile of PWV was 3.03 (95% CI 1.22-7.51, p=0.01) for significant EAT, 2.34 (95% CI 1.10-4.90, p=0.02) for significant PAT and 2.46 (95% CI 1.13-3.14, p=0.01) for significant CAC (CAC 100+) after adjustment for conventional cardiovascular risk factors. This relative risk was increased after combination of CAC 100+ with each significant adipose tissue. Conclusion: Increased vascular stiffness is associated with increase in EAT, PAT and coronary atherosclerosis. EAT was associated with higher relative risk of PWV, compared with CAC, suggesting a role of adipose tissue in vascular stiffness.
학위논문(박사)----아주대학교 일반대학원 :의학계열,2013. 8
Keywords: Vascular stiffness; Epicardial adipose tissue; Pericardial adipose tissue; Coronary atherosclerosis; Cardiac computed tomography